Kajian Tingkat Kecemasan Mahasiswa Dalam Menyusun Tugas Akhir Berdasarkan Visual Analogue Scales - Rusmita Sitorus; Idauli Simbolon (NUTRIX, 2023)
Based on preliminary research, students who are preparing research or final assignments experience many obstacles that cause anxiety. Anxiety is a condition that causes a person to feel uneasy, uncomfortable, afraid, worried, and uneasy about everything, which is followed by various physical symptoms. This research aims to determine the level of student anxiety in preparing their final assignment using quantitative descriptive methods by collecting data using a questionnaire that uses a visual analog scale (VAS). The results of this research showed that the anxiety scale of students who were completing their final assignments was in the heavy category. The tension scale of students who are completing their final assignment is in the medium category. The fear of failure scale of students who are completing their final assignment is in the severe category. The sleep pattern scale of students who are completing their final assignments is in the medium category. The concentration scale of students who are completing their final assignments is in the medium category. The depression scale of students who are completing their final assignment is in the medium category. There were differences in the scales of anxiety, tension, fear of failure, sleep patterns, concentration, and depression between men and women. There were differences in the scales of anxiety, tension, fear of failure, sleep patterns, concentration, and depression based on the type of final project (KTI, Thesis, and KIA). It is recommended to investigate further the factors that cause female students to be more anxious, more tense, more depressed and have sleep disorders than male students. Likewise, there are factors that cause male students to have more difficulty concentrating and are more afraid of failure than female students. Keywords: Anxiety, Final Assignments, Visual Analog Scale Abstrak Berdasarkan studi pendahuluan bahwa mahasiswa yang sedang menyusun penelitian ataupun tugas akhir banyak mengalami kendala yang menyebabkan kecemasan. Kecemasan merupakan keadaan dimana mengakibatkan seseorang merasa tidak tenang, tidak nyaman, rasa takut, khawatir, dan tidak tentram dalam segala hal sehingga diikuti berbagai gejala fisik. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan mahasiswa dalam menyusun tugas akhir dengan menggunakan metode deskriptif kuantitatif dengan pengumpulan data menggunakan kuesioner yang menggunakan visual analog scale (VAS). Hasil penelitian ini didapat bahwa skala cemas mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori berat. Skala tegang mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori sedang. Skala takut gagal mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori berat. Skala pola tidur mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori sedang. Skala konsentrasi mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori sedang. Skala depresi mahasiswa yang sedang menyelesaikan tugas akhir berada dalam kategori sedang. Ditemukan perbedaan skala cemas, tegang, takut gagal, pola tidur, konsentrasi, dan depresi antara laki-laki dan perempuan. Ditemukan perbedaan skala cemas, tegang, takut gagal, pola tidur, konsentrasi, dan depresi berdasarkan jenis tugas akhir (KTI, Skripsi, dan KIA). Disarankan untuk diteliti lebih lanjut faktor-faktor yang menyebabkan mengapa perempuan lebih cemas, lebih tegang, lebih depresi dan terganggu tidur dibanding laki-laki. Begitu juga dengan faktor-faktor yang menyebabkan laki-laki lebih sulit berkonsentrasi dan lebih takut gagal dibanding perempuan. Kata Kunci: Kecemasan, Tugas akhir, Visual Analogue Scales